Miró's posters - Corredor Matheos, José, 1929- (Ediciones Poligrafa, S. A., 1987)
Joan Miró's œuvre has been approached from widely differing angles. His artistic production comprises not only painting but also sketching, graphic work, sculpture, pottery, and tapestry. This book refers to one aspect that has been little dealt with, which has contributed moreover to the diffusion of his images to a wide public: the poster. A poster produced by the great artist fulfils the purpose of making known or proclaiming an event, but, at the same time, it is a Miró and must be recognised as such. Here we have a collection of the posters produced by him over a period of more than seventy years, with a very complete catalogue, by Gloria Picazo. The first of them, in 1917, was intended to advertise the Catalan magazine L ́Espagne (which we have reproduced on the dust-cover), published in 1937, at the height of the Spanish Civil War. From 1947 onwards, the year of the poster for the International Surrealism Exhibition in Paris, his activity in this field has been more and more intense. On numerous occasions the object was to advertise his own exhibitions; on others, collective demonstrations: acts of homage, conferences, books, and, in general, all kinds of cultural undertakings, with generosity and enthusiasm. Miró and his world constitute a key factor in the new image we have of the world. The influence exerted on new generations of artists has been as vast as it has it has been decisive. And the poster, devised precisely to act directly on the public, plays an important role in this. In Miró's case, the poster goes beyond its limits and we can rightly speak of a mural, with all the social implications involved. Having fulfilled its function of making known something very definite, it continues to be of interest precisely because it is art. -- Inside jacket flap.